Sistem Pengendalian Persediaan Stok Barang Pada Toko Hafiz Menggunakan Metode EOQ (Economic Order Quantity) - Makhfiroh, Tyka; Mugiarso, Mugiarso; Pamungkas, R. Wisnu Prio (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Inventory control needs to be considered by retail and manufacturing companies because it greatly determines the smooth running of business activities in achieving maximum profits with minimal costs. Inventory management of the Hafiz Store is still done manually. This can be overcome by having a prediction of the inventory that must be done to meet the number of customer requests. Prediction is expected to determine the optimal inventory. So the use of the Economic Order Quantity method in predicting demand for the next period is the right choice. The results of the analysis of yarn inventory control at the Hafiz Store concluded that the average demand for raw materials was 100 with an order cost of 1000, and a storage cost of 1000, with a period of 5 days, and the reorder point was 2550, the EOQ results obtained were 55. The prediction results are obtained then the process the calculation of the Economy Order Quantity (EOQ) method which is used to determine the number of items that must be ordered for each order, the amount of safety stock, and the minimum amount of stock for reordering through the built inventory application.